Field and Laboratory Evaluation of Pesticidal Plants for Bioactivity against Rape and Tomato Pests in Malawi - C. D. Kayange; S. P. Nyirenda; L. H. Mwamlima; J. F. Kamanula; C. R. Y. Munthali; D. Njera; P. Maluwa (Advances in Agriculture)
Insect pests cause serious damage through feeding in the process and may also transmit plant diseases. Although most resource-poor farmers rely on the use of synthetic insecticides for controlling insect pests, it is generally considered too expensive for them. Plant products may be a safer alternative approach and play a significant role in insect pest management and crop protection amongst resource-poor farmers. Laboratory and field evaluation of locally available pesticidal plants were evaluated. The study was conducted at Jenda and Nchenachena in Malawi with rape and tomato to assess the efficacy of some selected pesticidal plants for the control of vegetable pests. Largely, the choice of the selected pesticidal plants was based on resource-poor farmers’ knowledge in the area. The results of the tested plant extracts suggested that some plant extracts could reduce the infestation of red mites and aphids below economic threshold levels. Under laboratory experiments, all plant species caused a significant increase in mortality of Trypanosoma evansi after 24 h. However, Dolichos kilimandscarichus, Tephrosia vogelii, Azadirachta indica, and Bedotia madagascarensis had significantly at P<0.05 greater mite mortality than the untreated. This suggests that these pesticidal plants could be an alternative to acaricidal and insecticidal pesticides against vegetable pests. These pesticidal plants caused an impressive reduction of red mites and aphids and protected tomatoes and rapes from serious damage and hence could be incorporated into integrated management for the control of vegetable pests.